Exploring green entrepreneurship for global economic sustainability: A bibliometric and systematic review - Prasetio, Bayu; Supardi, Endang; Waspada, Ikaputera; Istikomah, Navik (Jurnal Ekonomi dan Bisnis, 2025)
This study explores the role of green entrepreneurship in supporting global economic sustainability through a systematic literature review and bibliometric analysis. Using data from the Scopus database and VOSviewer software, 19 relevant articles were analyzed to identify key trends and contributions. Findings show a significant increase in research on green entrepreneurship since 2017, peaking in 2024, driven by global sustainability agendas. Thematic analysis reveals six main roles of green entrepreneurship: integrating economic and environmental values, transforming industries, fostering green innovation and policy collaboration, creating green jobs and social innovation, strengthening MSMEs through sustainable digitalization, and embedding ethics and social justice in business practices. These roles highlight green entrepreneurship as a strategic driver of inclusive and resilient economic growth. The study concludes that green entrepreneurship delivers economic benefits and enhances social and environmental resilience. Future studies are encouraged to explore sector-specific practices and challenges, particularly in developing countries, and to expand cross-disciplinary approaches. A deeper understanding of policy support, technological innovation, and socio-environmental impact is essential to strengthen green entrepreneurship's role in sustainable development.